Antioxidant, Antiproliferative and Anti-Enzymatic Capacities, Nutritional Analysis and UHPLC-PDA-MS Characterization of Ungurahui Palm Fruits (Oenocarpus bataua Mart) from the Peruvian Amazon - Gabriel Vargas-Arana; Claudia Merino-Zegarra; Ángel Martín Rodríguez del-Castillo; Cristina Quispe; Ezequiel Viveros-Valdez; Mario J. Simirgiotis (MDPI AG, 2022)
Ungurahui, or Patawa, fruits are a popular fruit and medicinal food used in the Amazon. Here, we have studied nine natural populations of ungurahui from the Peruvian Amazon regarding their nutritional and biological activities, including metal composition, proximal analyses, cytotoxic, antioxidant and cholinesterase inhibition activities. Twenty-four compounds have been detected in these Peruvian natural populations by UHPLC-MS, including nine phenolic acids (peaks 1-6, 8, 9 and 11), four C-glycosyl flavonoids (peaks 12, 16, 17 and 18), two flavonols (peaks 7 and 10), one flavanol (peak 15), three anthocyanins (peaks 13, 14 and 22) and five resveratrol derivatives (peaks 19-21, 23 and 24). Sample 9, Tunaants, showed the highest DPPH clearing capacity regarding the content of Trolox equivalents (2208.79 μmol Trolox/g), but an ORAC test of the sample collected in San Lorenzo showed the highest clearing activity (1222.28 μmol Trolox/g) and the sample collected in Allpahuayo Mishana showed the most powerful ABTS (1803.72 μmol Trolox/g). The sample from Jenaro Herrera was the most powerful in AChe inhibition (IC50 2.05 ± 0.03 μg/mL), followed by the sample from Contamana (IC50 2.43 ± 0.12 μg/mL). In BChE inhibition, the sample from Palestina was the most active (4.42 ± 0.06 μg/mL), followed by samples from Tunaants and San Lorenzo. The differences among bioactivities can be related to the different growing conditions of the populations of ungurahui. The palm tree fruit proved to be a good source of natural antioxidants and dietary fatty acids, and their consumption represents an alternative for the prevention of neurodegenerative or related non-chronic transmittable diseases.